Intangibles : unlocking the science and soul of team chemistry - Ryan, Joan, 1959- (Little Brown & Company, 2020)
Does team chemistry actually exist? Is there scientific or mathematical proof? Is team chemistry as real and relevant as on-base percentages and wins above replacement? Team chemistry alone won't win a World Series, but talent alone won't win it, either. And by interviewing more than 100 players, coaches, managers, and statisticians, as well as over five years of extensive research in neuroscience, biology, physiology, and psychology, the author proves that the social and emotional state of a team does affect performance. Grit, passion, selflessness, and effort matter -- but never underestimate the power of chemistry.